Radiological diagnostic and treatment challenges of rare cases of adult fibrosarcoma: A case report - Yus, Teuku Muhammad; Syahri, Rahmat Alfi; Abdullah, Masna Dewi; Elvira, Nita; Ismida, Fitri Dewi (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Fibrosarcoma in adults is a rare malignant tumor originating from fibroblasts, accounting for 3% of all sarcomas in adults. We report the case of a 22-year-old man with a large, solitary, persistent mass on the right sole, accompanied by swelling and pain, as well as a mixture of blood and necrotic tissue. There was no history of trauma. Initial X-ray examination showed a soft tissue mass without periosteal reaction or bone damage. Ultrasonography confirmed the presence of a solid, slightly heterogeneous mass within the plantar fascia of the foot. Subsequently, Magnetic Resonance Imaging (MRI) showed an irregularly shaped solid mass with irregular margins, without a capsule, containing small areas of necrotic tissue, measuring approximately 7.4 x 4.4 x 4.3 cm in the right plantar fascia. The mass appeared to spread to the surrounding muscles without damaging the adjacent bones, with no evidence of neurovascular compression. Histopathological examination revealed highly proliferative fibroblastic cells arranged in a herringbone pattern. Fibroblastic cells with spindle-shaped nuclei, enlarged, coarse chromatin, and eosinophilic cytoplasm were present within the collagenous mass. The patient underwent tumor resection with clean margins of 1–2 cm, followed by chemotherapy, and is scheduled for radiotherapy. It is essential to perform appropriate radiological examinations and to correlate clinical, laboratory, and histopathological findings to diagnose fibrosarcoma and plan the best course of treatment.